Un pez que huye Cine latinoamericano 1991 - 2003 ; análisis estético de la producción - Caballero, Rufo 1966-2011 (Argos ensayo, 2007)
The book reviews the aesthetic elements of the new Latin America cinema analyzing in detail the topics and elements of selected films produced during the last decade in Argentina, Brazil, Chile, Colombia, Cuba, Venezuela and Mexico such as: Amores perros (Mexico, 2000), Ciudad de Dios (Brazil, 2002), Doña Brbara (Argentina, 1998), Fresa y chocolate (Cuba, 1993), Una casa con vista al mar, to mention a few. The book won first prize in 2004 on the category of essays on Latin American and Caribbean cinema